Second Five Year Plan Government of Rajasthan - Planning Commission (Planning Commission, 1956)
Rajasthan Government has conducted a detailed review of the targets of agricultural production as originally proposed in the Second Plan. As a result of this review the targets of agricultural production have been revised to ensure that as against 6 lakh tons of additional production of food grains, we will now produce 7.86 lakh tons by 1961 with the existing financial allocations. Apart from alterations of phasing and other steps, the higher additional production figure has been based upon the decision of the Government to cover all areas under irrigation projects with National Extension Service on a priority basis and to greatly expand the scope of short term production credit in the form of supply of improved seeds and fertilisers.
Government of Rajasthan, Planning and Development Department
Government of Rajasthan, Planning and Development Department